THE IMPACT OF READING BOOKS ON STUDENTS' CRITICAL THINKING - Eshpulatov Firdavs; Muratova Elmira (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Teaching students to think critically is super important these days. This paper looks at how reading books helps students get better at it. When students read, they have to figure things out, think about different ideas, and decide what makes sense. By reading different kinds of books and really thinking about what they're reading, students get better at thinking for themselves. So, schools should make reading a big part of learning to help students become independent thinkers.